HEDGING THROUGH THE USE OF IMPERSONAL CONSTRUCTIONS IN INDONESIAN OP-ED ARTICLES - Devi Nailis Yusnia; Tofan Dwi Hardjanto (Linguistik Indonesia, 2023)
The presence of an opinion editorial (op-ed) page has provided room for the public to articulate their ideas about the recent salient issues at no cost. The notion that the authors of an op-ed article could express their ideas and arguments in public space makes them need certain devices like hedges to protect themselves from any negative consequences such as rejection from readers if in fact their argument is considered false. This article is intended to investigate the use of impersonal constructions as hedging devices in 45 Indonesian opinion editorial articles published by three leading national newspapers: Kompas, Tempo, and Republika. Impersonal construction in this case refers to a grammatical construction that avoids the use of a human subject in the sentence. This construction includes the use of agentless passive voice and abstract rhetors. A qualitative research design is applied in this study. This study reveals 56 occurrences of impersonal construction with details of 53 data belonging to the agentless passive voice category and 3 data belonging to the abstract rhetors category in the 45 articles examined.Â  The use of such constructions in op-ed articles can be a means to protect the authors from the consequences of being blamed if in any case, the argument they stated is different from the reality. Furthermore, this construction can also be used to avoid the subjectivity of the claim and direct the focus of the argument to the content of the text and not the authors.Â